CYBER CULTURAL COUNSELLING AS AN ALTERNATIVE TO PROBLEM SOLVING CULTURE SHOCK OF STUDENTS WHILE DISTANCE LEARNING DURING THE COVID-19 PANDEMIC IN INDONESIA (International Conference on Social and Islamic Studies, 2021)
The purpose of this research is to answer the problems of education in Indonesia during the Covid-19 pandemic. One form of this problem is the phenomenon of culture shock faced by students during online distance learning. It is caused due to the change of learning environment. The form of culture shock is that students feel anxious and nervous when they have to carry out distance learning. This research approaches literature study by collecting various sources of data. The results of this study indicate that cyber multicultural counselling is a multicultural counselling service that is carried out remotely. The focus of this counselling is to help students to be able to adapt to new situations and conditions, from face-to-face learning culture to distance learning. Then the measure that multicultural cyber counselling really becomes an alternative problem-solving shock culture is asfollows. First, students need to adapt to the new environment and culture in the learning process, therefore special attention needs to be paid to understanding the conditions of the learning culture that is currently changing. The special attention is in the form ofproviding direction, support, and motivation that the Covid-19 pandemic condition does require adaptation. Second, namely the psychological condition of students who tend tobe unstable in accepting new things, such as the Covid-19 pandemic. The unstable psychological condition is caused by the limited mindset of students regarding the current conditions that actually occur. Therefore, there needs to be proper handling so that the psychological condition of students is able to understand the conditions of the Covid-19 pandemic. The handling is by providing educational entertainment that can be providedby the BK teacher. The form of educative entertainment is adjusted to the creative abilities and competencies of the BK teachers in each school. The third is multicultural cyber counselling as a form of support for the government to carry out social distancing and psychological distancing so that the Covid-19 pandemic can be completed and can minimize the spread of Covid-19 in school clusters.